Inhibition of SMYD2 suppresses tumor progression by down-regulating microRNA-125b and attenuates multi-drug resistance in renal cell carcinoma - Yan, Libin (Theranostics, 2019)
SMYD2 is a histone methyltransferase that has been reported to be an important epigenetic regulator. This study aims to investigate SMYD2 as a prognostic indicator of clear cell renal cell carcinoma (ccRCC) and explore its role in tumorigenesis and multi-drug resistance. Methods: Tumor specimens, clinicopathologic information, and prognostic outcomes of 186 ccRCC patients from three hospitals in China were collected for SMYD2 immunohistochemistry staining, Kaplan-Meier analysis, and Cox proportional hazards-regression analysis. MicroRNA (miRNA)-microarray profiling identified differentially expressed miRNAs in renal cancer cells subjected to SMYD2 knockdown or treatment with the SMYD2 inhibitor AZ505. The effects of SMYD2 and candidate SMYD2-mediated miRNAs on renal cancer cell proliferation, migration, clonogenicity, and tumorigenicity were determined via cell-function assays and murine xenograft experiments. The half-inhibitory concentrations (IC(50)) of five antineoplastic drugs (cisplatin, doxorubicin, fluorouracil, docetaxel, and sunitinib) in AZ505-treated and control cells were calculated, and the effects of SMYD2 inhibition on P-glycoprotein (P-gP) expression and multiple-drug resistance were verified. Results: SMYD2 was overexpressed and acted as an oncogene in ccRCC. High SMYD2 expression correlated with a high TNM stage (P = 0.007) and early tumor relapse (P = 0.032). SMYD2 independently predicted a worse overall survival (P = 0.022) and disease-free survival (P = 0.048). AZ505 inhibited the binding of SMYD2 to the miR-125b promoter region (based on chromatin immunoprecipitation assays) and suppressed ccRCC cell migration and invasion by inhibiting the SMYD2/miR-125b/DKK3 pathway. SMYD2 and miR-125b inhibition acted synergistically with anticancer drugs via P-gP suppression in vitro and in vivo. Conclusions: These findings suggested that SMYD2 plays an important role in ccRCC development and could be a potential biomarker for the treatment and prognosis of RCC.